Z‐scores of fetal bladder size for antenatal differential diagnosis between posterior urethral valves and urethral atresia. (1st December 2021) - Fontanella, F.; Groen, H.; Duin, L. K.; Suresh, S.; Bilardo, C. M.
ABSTRACT: Objective: To construct reference values for fetal urinary bladder distension in pregnancy and use Z ‐scores as a diagnostic tool to differentiate posterior urethral valves (PUV) from urethral atresia (UA). Methods: This was a prospective cross‐sectional study in healthy singleton pregnancies aimed at constructing nomograms of fetal urinary bladder diameter and volume between 15 and 35 weeks' gestation. Z ‐scores of longitudinal bladder diameter (LBD) were calculated and validated in a cohort of fetuses with megacystis with ascertained postnatal or postmortem diagnosis, collected from a retrospective, multicenter study. Correlations between anatomopathological findings, based on medical examination of the infant or postmortem examination, and fetal megacystis were established. The accuracy of the Z ‐scores was evaluated by receiver‐operating‐characteristics (ROC)‐curve analysis. Results: Nomograms of fetal urinary bladder diameter and volume were produced from three‐dimensional ultrasound volumes in 225 pregnant women between 15 and 35 weeks of gestation. A total of 1238 urinary bladder measurements were obtained. Z ‐scores, derived from the fetal nomograms, were calculated in 106 cases with suspected lower urinary tract obstruction (LUTO), including 76 (72%) cases with PUV, 22 (21%) cases with UA, four (4%) cases with urethral stenosis and four (4%) cases with megacystis‐microcolon‐intestinal hypoperistalsis syndrome. Fetuses with PUV showed a significantly lower LBD Z ‐score compared to those with UA (3.95 vs 8.83, P < 0.01). On ROC‐curve analysis, we identified 5.2 as the optimal Z ‐score cut‐off to differentiate fetuses with PUV from the rest of the study population (area under the curve, 0.84 (95% CI, 0.748–0.936); P < 0.01; sensitivity, 74%; specificity, 86%). Conclusions: Z ‐scores of LBD can distinguish reliably fetuses with LUTO caused by PUV from those with other subtypes of LUTO, with an optimal cut‐off of 5.2. This information should be useful for prenatal counseling and management of LUTO. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.